Conformation Transition of Intracellular Part of Glucagon Receptor in Complex With Agonist Glucagon by Conventional and Accelerated Molecular Dynamics Simulations - Bai, Qifeng; Tan, Shuoyan; Pérez-Sánchez, Horacio; Feng, Haixia; Feng, Liya; Liu, HuanXiang; Yao, Xiaojun (Frontiers in Chemistry, 2019)
The inactive conformations of GCGR are widely reported by crystal structures which support the precision structure for drug discovery of type 2 diabetes. The previous study shows the intracellular part is open in the glucagon-bound GCGR (glu-GCGR) and closed in the apo-GCGR by accelerated molecular dynamics (aMD) simulations. However, the crystal structure of GCGR in complex with partial agonist shows the intracellular part is closed in the inactive conformation. To understand the differences between the studies of aMD simulations and crystal structure, the 2500 ns conventional molecular dynamics (cMD) simulations are performed on the simulated model of glu-GCGR. The result shows the transmembrane helices (TMH) 6 of glu-GCGR is outward ~4 Å to drive intracellular part of glu-GCGR open until ~390 ns cMD simulations. The transmembrane helices (TMH) 6 of glu-GCGR becomes closed after ~490 ns cMD simulations which are consistent with crystal structure of GCGR in complex with partial agonist. To further elucidate the activation mechanism of GCGR deeply, the simulated models of glu-GCGR, apo-GCGR and antagonist-bound GCGR (ant-GCGR) are constructed to perform 10 of parallel 300 ns aMD simulations, respectively. The results show both of glu-GCGR and apo-GCGR can generate the open conformations of intracellular part. But the glu-GCGR has the higher percentage of open conformations than apo-GCGR. The ant-GCGR is restricted to generate the open conformations of intracellular part by antagonist MK-0893. It indicates that the glu-GCGR, apo-GCGR and ant-GCGR can be distinguished by aMD simulated method. Free energy landscape shows the open conformations of intracellular part of GCGR are in intermediate state. Our results show aMD simulations enhance the space samplings of open conformations of GCGR via adding extra boost potential. It indicates that the aMD simulations are an effective way for drug discovery targeted GCGR.